Coping Strategies to Climate Related Events Across the Gradient of Three Agro-ecological Zones of Same District, Tanzania - Bakari, Aroni; Liwenga, Emma; Perfect, Joseph (Tanzania Journal for Population studies and Development, 2025)
This study assessed coping strategies used to climate related events across the gradient of three agro-ecological zones of Same District, Tanzania. Data was collected through household survey, key informant interviews, focus group discussions, and review of documents. Quantitative data was analysed using SPSS and XLSTAT, while qualitative data was analysed using content analysis. A forty-year climatic trend analysis depicts changes in both temperature and precipitation, and there is a significant difference in drought occurrence (p=0.0000) among the study villages, with high frequencies of occurrence recorded in Bangalala and Jiungeni compared to Malindi. The year 1974 was affirmed as a difficult year ever experienced in the study area, characterized by prolonged drought. Jiungeni frequently experienced floods, while Bangalala and Malindi never experienced floods. Climate stress events affected the livelihood of the people including damaging crops which resulted in low crop yields,reduction in pastures for livestock, increased livestock diseases, reduction in water sources, increased crop pests and diseases, and reduction in crop varieties. The extent of the impact of local climate change was significantly felt in the lowland areas because floods and drought were predominant in these areas. To cope with climatic stress, different coping strategies are employed by local communities like eating of neglected and underutilized plant species like red amaranth and spiderwisp, moving livestock to Tanga and Kiteto, eating fewer meals per day, looking for food relief aid, and the selling of forest products.